Microcredit impact on children's education and women empowerment: A review experience of grameen bank microfinance schemes in bangladesh - Abul Bashar, Bhuiyan, Dr. (Maxwell Scientific Organization, 2014)
Link to publisher's homepage at http://maxwellsci.com/